Performance and stability of ether-free high temperature proton exchange membranes with tunable pendent imidazolium groups. Issue 47 (24th November 2022) - Ju, Qing; Tang, Hongying; Chao, Ge; Guo, Tiegen; Geng, Kang; Li, Nanwen
Abstract : Side-chain imidazolium–phosphate ion pairs PEMs with regulated imidazolium content were constructed by copolymerization and subsequent methylation processes. Abstract : (Benz)imidazoliums are demonstrated to be effective for the retention of phosphoric acid (PA) in PA doped proton exchange membranes (PEMs) due to the formation of (benz)imidazolium–biphosphate ion-pairs. However, there is less research on the stability of the polymer materials with pendent (benz)imidazoliums. Herein, novel ether-free poly(biphenyl isatin- co -imidazolium)s (PIBI-Q x ) were prepared as PA doped PEMs via a one-step superacid catalysed polycondensation and methylation process. The dissolution of PA/PIBI-Q x membranes at high temperature can be inhibited effectively via tuning the methylation degree of the pendent imidazole. Moreover, the PA retention and conductivity retention of the PA/PIBI-Q70 (70% imidazolium content) membrane are over 20% and 30% higher than those of the PA/ m PBI membrane, respectively, after 100 h at 80 °C/40%RH. Thus, the corresponding cell is stable for at least 60 h at 160 °C with 8% RH, while a significant drop of 27% in the peak power density is observed for the PA/ m PBI membrane-based cell. Furthermore, the thermal/acidic stability of PIBI-Q x membranes with pendent imidazolium groups was studied, and two dominating degradation mechanisms e.g. "de-methylation" of imidazolium and "retro-Friedel–Crafts reaction" in the polymer backbone are verified via XPS spectral analysis.